2016
DOI: 10.1186/s12904-016-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of reflective diaries in end of life training programmes: a study exploring the impact of self-reflection on the participants in a volunteer training programme

Abstract: BackgroundA training programme was developed and delivered to a cohort of volunteers who were preparing for a unique role to provide companionship to dying patients in the acute hospital setting. This comprehensive programme aimed to provide an opportunity for participants to fully understand the nature and responsibilities of the role, whilst also allowing sufficient time to assess the qualities and competencies of participants for their ongoing volunteering role.Participants completed reflective diaries thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Reflective diaries have long been advocated as a method to bridge the gap between theory and practice in other occupational groups with high levels of interpersonal demands, including nurses and teachers. [49][50][51] This study has shown that home care workers are not only happy to keep reflective diaries but also that in doing so they derive benefits, both personal and professional, while contributing to a fuller understanding of the essential ingredients of good home care. By implication, this might be true for other occupational groups who are also relatively voiceless, or whose work is done out of sight.…”
Section: Discussionmentioning
confidence: 91%
“…Reflective diaries have long been advocated as a method to bridge the gap between theory and practice in other occupational groups with high levels of interpersonal demands, including nurses and teachers. [49][50][51] This study has shown that home care workers are not only happy to keep reflective diaries but also that in doing so they derive benefits, both personal and professional, while contributing to a fuller understanding of the essential ingredients of good home care. By implication, this might be true for other occupational groups who are also relatively voiceless, or whose work is done out of sight.…”
Section: Discussionmentioning
confidence: 91%
“…Practicing self-reflection in end of life can enable people to identify their feelings (30).. and consider the influence of these on their practice (33). Self-awareness is necessary for the personal and professional development of nurses (34,35) Lack of knowledge and confidence can inhibit nurse's ability to have an active role in supporting people in palliative care, and healthcare professionals can experience challenges with initiating conversations relating to death (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…57 More recently, novel initiatives have involved training volunteers in hospitals for specific roles related to palliative and EoLC. For example, in the United States, Sanon et al 58 trained hospital volunteers to support older people admitted to emergency departments, while in the United Kingdom, Germain et al 59 trained volunteers for a Care of the Dying Volunteer Service (designed for wards with high numbers of deaths and palliative care referrals). However, our study findings highlight that hospital volunteers in general support roles also encounter many challenges related to EoLC.…”
Section: Discussionmentioning
confidence: 99%